Immunogenicity of Conjugated and Polysaccharide Pneumococcal Vaccines Administered During Pregnancy or Postpartum to Women With HIV - Duarte, Geraldo (2021)
Universidade de São Paulo. Escola de Medicina de Ribeirão Preto. Departamento de Ginecologia e Obstetrícia. Ribeirão Preto, SP, Brasil.